2016
DOI: 10.1021/acsami.6b09480
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Electric-Field-Assisted Annealing and Thermal Annealing in Bulk-Heterojunction Solar Cells

Abstract: We propose an optimum low-temperature-based annealing procedure for semicrystalline donor-fullerene solar cells that is well-suited for plastic and flexible substrates. This proposed alternate strategy utilizes an external electric field (EF) across the bulk heterojunction (BHJ) film during processing at a desired temperature. This processing technique is studied for different molecular weights of the donor in the BHJ blend films. The films indicate an increase in interchain interactions of the semicrystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…These results are consistent with our earlier studies of GIWAXS where EF(+) treatment was carried out on P3HT: PC 70 BM BHJ films. [6a] The XRD peak of polymer donor around Q value of 0.31 A −1 , corresponds to the alkyl interchain interaction (100) . The lower intensity of the PTB7‐Th peak reflects the amorphous nature of the donor polymer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with our earlier studies of GIWAXS where EF(+) treatment was carried out on P3HT: PC 70 BM BHJ films. [6a] The XRD peak of polymer donor around Q value of 0.31 A −1 , corresponds to the alkyl interchain interaction (100) . The lower intensity of the PTB7‐Th peak reflects the amorphous nature of the donor polymer.…”
Section: Resultsmentioning
confidence: 99%
“…EFTA‐treated devices exhibit nominal efficiency and higher stability when compared with control devices. The EFTA treatment involves an application of external DC electric field (EF) during TA of active layer . Earlier studies on EFTA treatment were focused on semicrystalline donor polymer; primarily, semicrystalline donor (P3HT‐based BHJs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various synthesis parameters [6][7][8][9][10][11][12][13][14], the effects of the application of electric field during synthesis or as a postproduction treatment have shown improvements in the PCE [11,[15][16][17][18][19][20][21][22]. A better understanding of the electric field treatment will provide great insights on further improving the OPVC performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors were also discussed in literature, such as the elimination of the nano-domains (better intermolecular mixing) [32] or the rougher surfaces for better contact [24]. In some works, the electric field dependence experiments showed that there exists a certain optimized electric field strength for the optimal OPVC performance [20][21][22]. This observation indicates that the electric field treatment may induce both positive and negative impacts on the OPVC performance.…”
Section: Introductionmentioning
confidence: 99%